Intraoperative seizures in Low Grade Gliomas surgery: From electrocorticography to molecular pattern. Issue 1 (January 2019) - Lettieri, C.; Pauletto, G.; Ius, T.; Cesselli, D.; Cerretti, G.; Budai, R.; Skrap, M.
Abstract : Few and contradictory data are available regarding intraoperative seizures (IOS) during surgery for Low Grade Gliomas (LGGs). Aim of this study was to evaluate the occurrence of IOS in regard to pre-operative clinical data, tumor molecular characteristics and electrocorticographic patterns. We performed a retrospective analysis of 155 patients affected by LGGs and tumor-related epilepsy, who underwent surgery in our Department, between 2007 and 2017. Pre-operative seizures frequency was as follows: 59% monthly, 34% weekly and 11% daily. 73% of patients were operated on through awake surgery. IOS occurred in 39 patients: in 9 patients only electrographic seizures occurred while in 13 patients seizures were cognitive, sensory, autonomic or emotional, thus recognizable only by means of electrocorticography (ECoG). Nineteen seizures were induced by brain mapping. Patients with ECoG epileptiform inter-critical patterns and IDH1/2 mutated tumors or oligodendrogliomas were more likely to develop IOS (p < 0.001). The occurrence of IOS did not affect post-operative seizure outcome, being most of the patients in Engel class I, at one-year follow up. High frequency of seizures, IDH 1/2 mutated tumor and epileptiform ECoG pattern are risk factors for IOS. ECoG is necessary to detect electrical or subtle seizures.